Pengaruh Illness Perception dan Stigma terhadap Perilaku Help-Seeking Caregiver pada Penderita Psychosis - Iqlima Faradila; Farida Coralia (Bandung Conference Series: Psychology Science, 2023)
Abstract. The stigma that develops in people with psychosis causes caregivers to be reluctant to seek professional help. On the other hand, each individual has a representation in interpreting a disease and what is being done to overcome it. This study aims to determine the effect of the perception of illness and stigma on the behavior of seeking help in people with psychosis. This research is a quantitative research with causality method. This research uses purposive sampling. The subjects of this study were family caregivers for people with psychosis with the characteristics of people with psychosis having been diagnosed by professionals and domiciled in Bandung Raya, which collected 25 people. The data analysis method used multiple linear regression. Data was collected using the The Brief Illness Perception Questionnaire (B-IPQ) from Broadbent adapted by Rias, The Internalized Stigma of Mental Illness Inventory (ISMI-9) from Hammer & Toland adapted by Nurcahyati, and Attitudes Toward Seeking Professional Psychological Help Short Form (ATSPPH-SF) from Picco adapted by Nurdiyanto. The results of the study were 88% of caregivers had a positive perception of illness, 76% of caregivers were found to have negative stigma, and 64% of caregivers had high help-seeking behavior. The results of the T test show that only the perception of the disease affects the behavior of seeking help. The results of the F test showed that the perception of disease and stigma simultaneously contributed 37.6% to the behavior of seeking help for caregivers in people with psychosis. Abstrak. Stigma yang berkembang pada penderita psychosis mengakibatkan caregivernya enggan mencari pertolongan professional. Disisi lain, setiap individu memiliki gambaran dalam memaknai suatu penyakit dan apa yang dilakukan untuk mengatasinya. Penelitian ini bertujuan untuk mengetahui pengaruh antara illness perception dan stigma terhadap perilaku help-seeking pada penderita psychosis. Penelitian ini merupakan penelitian kuantitatif dengan metode kausalitas. Penelitian ini menggunakan purposive sampling. Subjek dari penelitian ini adalah family caregiver pada penderita psychosis dengan karakteristik penderita psychosis sudah didiagnosa oleh professional dan berdomisili di Bandung Raya yang berjumlah 25 orang. Metode analisis data menggunakan regresi linear berganda. Pengumpulan data dilakukan menggunakan alat ukur The Brief Illness Perception Questionnaire (B-IPQ) dari Broadbent yang diadaptasi oleh Rias, The Internalized Stigma of Mental Illness Inventory (ISMI-9) dari Hammer & Toland yang diadaptasi oleh Nurcahyati, dan Attitudes Toward Seeking Professional Psychological Help Short Form (ATSPPH-SF) dari Picco yang diadaptasi oleh Nurdiyanto. Hasil penelitian ditemukan 88% caregiver memiliki illness perception yang positif, 76% caregiver memiliki stigma yang negatif, dan 64% caregiver memiliki perilaku help-seeking yang tinggi. Hasil uji T menunjukkan hanya illness perception yang berpengaruh terhadap perilaku help-seeking. Hasil uji F menunjukkan illness perception dan stigma secara simultan memberikan kontribusi sebesar 37.6% terhadap perilaku help-seeking caregiver pada penderita psychosis.